Career shift and career services in college - Munadi, Muhammad; Umar, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aims to determine the relationship between independent competency standards of students with career development, career shift trends, and the relationship between extracurricular activities and student career development in College. This research method uses document studies about the ins and outs of career development in College. I collected documents from the Guidance and Counseling Implementation Guidelines in Formal Education published by the Directorate General of Teachers and Education Personnel of the Ministry of Education and Culture in 2016, publications related to career development, and publications from McKinsey. It analyzed the data using descriptive qualitative analysis. The result of this research is that the standard of self-reliance competence has been optimized integratively by institutions in College through career service activities. These activities are extracurricular, co-curricular, extracurricular cooperation between lecturers. It can carry activities in College to prepare students to face the trend of shifting community careers at the local, national, and global levels.